Room‐temperature self‐healing and reprocessing of Diselenide‐containing waterborne polyurethanes under visible light. Issue 7 (19th September 2018) - Fan, Wuhou; Jin, Yong; Huang, Yuhua; Pan, Jiezhou; Du, Weining; Pu, Zongyao
ABSTRACT: Realizing environmentally friendly polymers that could heal themselves at room temperature is an important challenge for sustainable societies. Herein, environment‐friendly self‐healing waterborne polyurethanes (WPUs) containing diselenide groups were synthesized. The healing efficiency could reach up to more than 90% after exposed to visible light for 48 hours and the fractured location was allowed to be healed repeatedly. Meanwhile, a fast room‐temperature self‐healing could also be achieved in 4 hours with a healing efficiency of ~84%. The healing process was a combination of rapid closure of crack surfaces at the beginning due to the rebuilding of hydrogen bonds and gradual restoration of mechanical property derived from diselenide metathesis across the fractured interface. At the same time, room‐temperature reprocessing could be also achieved with the aid of external pressure under visible light. Moreover, the prepared diselenide‐containing WPUs exhibited excellent emulsion stability. The present work would be hopefully developed into a methodology of design and fabrication of environmentally friendly photo‐sensitive polymers with self‐healing and reprocessing abilities. © 2018 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2019, 136, 47071. Abstract :